1990
DOI: 10.1002/path.1711610315
|View full text |Cite
|
Sign up to set email alerts
|

QBEnd/10: A new immunostain for the routine diagnosis of Kaposi's sarcoma

Abstract: Kaposi's sarcomas are seen more commonly in routine histopathology laboratories since the advent of the more widespread and aggressive variant of the disease associated with HIV infection. Distinguishing nodular lesions from other spindle cell and vascular tumours can sometimes be difficult. Immunohistochemistry has been disappointing as a diagnostic aid, often requiring special fixation or frozen tissue and even then, staining of spindle cells has been variable. We describe the use of the new IgG1 mouse monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 11 publications
4
24
0
2
Order By: Relevance
“…Both the proportion and density of VEGF-A expression were shown to be positively correlated with colon carcinogenesis [13] and it has been demonstrated that low levels of VEGF, as assessed by IHC, predicted for eventfree survival in node-negative colon cancer [14]. This confirms the previous work of a number of authors, including Takahashi et al [19], who showed that overexpression of VEGF and its receptor (KDR) predicted for metastasis.…”
Section: Discussionsupporting
confidence: 79%
“…Both the proportion and density of VEGF-A expression were shown to be positively correlated with colon carcinogenesis [13] and it has been demonstrated that low levels of VEGF, as assessed by IHC, predicted for eventfree survival in node-negative colon cancer [14]. This confirms the previous work of a number of authors, including Takahashi et al [19], who showed that overexpression of VEGF and its receptor (KDR) predicted for metastasis.…”
Section: Discussionsupporting
confidence: 79%
“…Our results strongly affirm the superb sensitivity of antibodies to VEGFR-3 for KS; the spindle cells in 24 of 25 cases of KS, at all stages of development and including metastatic lesions, were strongly positive for VEGFR-3. The sensitivity of anti-VEGFR-3 in paraffin-embedded sections (96%) compares very favorably to that reported for CD31 (89%) (5), CD34 (93%) (19), and vWF (64%) (20). Our findings of slightly greater sensitivity for CD31 (93%) and vWF (79%) may be the result of our uniform use of heat-induced epitope retrieval.…”
Section: Discussionsupporting
confidence: 75%
“…The CD34 antigen, also known as human haematopoietic progenitor cell antigen, is a heavily glycosylated transmembrane protein expressed on immature human haematopoietic precursor cells from normal bone marrow, and in a significant number of acute leukaemias [3,4,6,21,23,41]. Several studies have demonstrated CD34 antigen expression in vascular endothelium [10, 33], and in endothelial derived tumours [20,39], especially Kaposi's sarcoma [11,19,28,33,34].…”
Section: Introductionmentioning
confidence: 99%